Analisis Kualitas Pelayanan Room Attendant Terhadap Kepuasan Pelanggan Di Hotel Inter- Continental Jakarta Mid Plaza - Taviprawati, Ervina; Sembiring, Vienna Artina; Tarigan, Emenina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
Increasingly intense competition in the service or service industry, making hotel organizations strive to always improve the quality of service in accordance with customer demand at present (short term), as well as future (long term) so that customers feel satisfied and continue to use services. One important hotel service is Housekeeping department because it has a role to support cleanliness, neatness, and beauty of the room. To provide quality room service standards, behavior and actions of Room Attendant must be properly considered where the room attendant must understand how to serve and understand the guests, because providing quality services to guests has the purpose of winning business competition. The research method used is the Importance-Performance Analysis method at the Inter-Continental Hotel Jakarta Mid-Plaza for 1 month, from August untillseptember 2017 with 75 guest that stay in the hotel. Analysis of customer satisfaction. the advantage of this method is the using of measurement methods that are easy to understand. This method is done by measuring five dimensions of service quality, tangible, reliability, responsiveness, assurance, empathy. The results of the assessment show that the average room attendant performance is slightly higher than the average guest expectation, so guests staying at the Inter-Continental Hotel Jakarta Mid-Plaza are satisfied with the service of the room attendant